Catalytic one-handed helix-induction and memory of amphiphilic poly(biphenylylacetylene)s in water. (June 2020) - Ikai, Tomoyuki; Mizumoto, Kosuke; Ishidate, Ryoma; Kitzmann, Winald R.; Ikeda, Riho; Yokota, Chiaki; Maeda, Katsuhiro; Yashima, Eiji
Highlights: First catalytic helicity induction and memory of the helicity in water. Perfect solvent-dependent helicity inversion between water and organic solvents. Bidirectional chiral amplification achieved in achiral/chiral helical copolymers. Chiral discrimination using water-soluble one-handed helical polymers in water. Circularly polarized luminescence induced by helicity-memorized helical polymers. Abstract: A series of amphiphilic biphenylylacetylene-based homo- and copolymers (PBPAs) carrying chiral and/or achiral oligo(ethylene glycol) pendants at the 4′-position of the biphenyl units were synthesized and the amplification of the macromolecular helicity through noncovalent and/or covalent chiral interactions followed by the memory of the helicity were investigated in both water and organic solvents. The macromolecular helicity was efficiently induced in the homopolymers of achiral monomers through specific encapsulation of a catalytic amount of hydrophobic chiral guests in water and their induced helicities were stably memorized in water after complete removal of the optically-active guests, while an excess helical sense was not biased at all in the homopolymers in toluene. One-handed macromolecular helicities were also efficiently induced in the chiral homopolymers through chiral information transfer from covalently linked optically-active pendants with a point chirality to biphenyl units with a dynamic axial chirality, whose helical senses were almost perfectly inverted in water and organic solvents. The achiral/chiral copolymers displayed a unique bidirectional ( P and M ) strong chiral amplification of the macromolecular helicity in water and toluene assisted by the solvent-induced helix-inversion, and their macromolecular helicities were further enhanced or inverted through encapsulation of a catalytic amount of enantiomeric alcohols in water, which could be further memorized in water after removing the encapsulated guests. We also demonstrated that the left- and right-handed circularly polarized lights could be generated through chirality transfer from the one-handed helical polymers with a macromolecular helicity memory, consisting entirely of achiral monomer units, to an achiral fluorescent dye in the blended films. Importantly, the resulting luminescence dissymmetry factors (ca. 2 × 10 –3 ) were virtually the same as those of chiral homopolymers composed of the optically-pure repeating units. Graphical abstract: Image, graphical abstract